My clinical clerkship diary / Nur Ainin Sofiya Mohamad Irwan and Dr. Gurmeet Kaur Surindar Singh - Mohamad Irwan, Nur Ainin Sofiya; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
June—has it arrived? I could not wait! I was overly enthusiastic, and the clinical rotation would be fun! It was when you were finally able to apply the clinical knowledge you had learned in the classroom. It was the time I had looked forward to since my junior year, and of course, I am most excited about this! I would say the clinical clerkship is the perfect start for an insight into the job scope as a clinical pharmacist prior to leaving the university and stepping into the life of housemanship. As for UiTM, the clerkship will cover three different modules for the fourth-year students to complete. This includes tele-pharmacy, hospital, and Clinical Pharmacy Simulation (CLIPS) modules.